NEONATE OUTCOME AND RESPONSE TIME FOR EMERGENCY CESAREAN SECTION : A SCOPING REVIEW - Diah Melly Marlyana; Atik Nurwahyuni; Adik Wibowo (Fakultas Kedokteran Universitas Sriwijaya, 2023)
Emergency CS response time guidelines by National Institute for Health Care Excellence (NICE) were difficult to implement in many countries and these constraints have led to poor neonate outcome in several previous study. This research aim to determine the affordability of emergency CS response time based on NICE recommendation and its correlation to neonate outcome in lower-middle income countries and factors related to the response time. This scoping review data was extracted from several electronic data bases, which was accessed in February – March 2022, applying the PRISMA-ScR approach. Six eligible studies that meet inclusion criteria from 4,992 articles were obtained and analyzed. the average DDI achievement percentage was still lower than 20% in 5 studies, unless study from Gupta with DDI‘s achievement 42.4%. The response times recommended by NICE can‘t be met in many lower-middle-income countries with limited resources, factors related to delayed response times need to be corrected.